Substitute in Making Pizza with Jackfruit Seed Flour - Nompo, Fadhli Dzil Ikram; Saleha, Saleha; Utami, Nisa Rahmaniyah (Media Pendidikan Gizi dan Kuliner, 2024)
This research aims to replace some basic ingredients in pizza with jackfruit seed flour, as it has a low gluten content and is safe for consumption. Researchers conducted organoleptic tests and hedonic tests on 35 non-expert panelists and 5 expert panelists to determine their preferences. The results showed that jackfruit seed flour could be added as a basic ingredient for making pizza. The most preferred pizza product made from a mixture of jackfruit seed flour was Product 3 (70% wheat flour and 30% jackfruit seed flour), with expert panelists scoring 12.6 with an average value of 3.15, and non-expert panelists scoring 14.08 with an average value of 3.52. The results suggest that jackfruit seed flour can be used as a basic ingredient for making pizza, reducing the negative impact of wheat flour on health.